Hubungan optimisme karir dan kesuksesan karir subjektif pada guru - Apriliani, Enana; Ingarianti, Tri Muji (Universitas Brawijaya, 2023)
The lack of fulfillment of teachers' rights has resulted in teachers feeling less prosperous and less satisfied with their current careers. In order to feel career satisfaction, teachers need a measure of subjective career success. Achieving subjective career success requires career optimism so that teachers can view their future career positively, focus on developing their potential, and plan their career path. The objective of this study is to determine the relationship between career optimism and the eight dimensions of subjective career success among teachers. The study used quantitative methods and quota sampling techniques with a total of 300 participants. The result of the study showed that career optimism is significantly related with the five dimensions of subjective career success, (i.e., authenticity, growth and development, influence, personal life, and satisfaction). Moreover, career optimism is not significantly related with the three other dimensions of subjective career success (i.e. meaningful work, quality of work, and recognition).